Relationship between Internet use and offline leisure activities among Chinese older adult people: a moderated mediation model - Shuai Xiang; Qinwen Deng; Boli Chen (Frontiers in Public Health)
BackgroundThe process of aging in Chinese society is accompanied by the concurrent development of the Internet. In recent years, the influence of Internet use on the activities of older adults has attracted growing interest and is now a significant focus of both public health and gerontological research. Nevertheless, there is a need for further empirical research in this area.PurposeThis study aimed to examine the mechanisms and interaction processes, as well as the relationship between Internet use and offline leisure activities among Chinese older adults. Theories of active aging and environmental gerontology guided the construction and assessment of the mediating role of self-perception of aging between Internet use and offline leisure activities. Additionally, the moderating role of community-based leisure places (CBLP) was examined.MethodsA moderated mediation model was constructed using the SPSS 27 PROCESS Macro. This study employs the most recent China Longitudinal Aging Social Survey (CLASS) 2020 cross-sectional data, and the valid sample comprises 8,180 Chinese older adult individuals aged 60 years or older.Results(1) Internet use and offline leisure activities among older adults exhibited a significant positive correlation. (2) Self-perception of aging played a significant positive mediating role between Internet use and offline leisure activities. (3) CBLP significantly and positively moderated the relationship between Internet use and offline leisure activities.ConclusionThe Internet can be an effective tool for addressing the challenges of aging. Active Internet use may lead to more positive age perception and more active offline leisure activities, and efforts should be made to increase the digitization of the aging society. Positive self-perception of aging is an important psychological factor influencing the offline and online activities of older adults. It is imperative that the concept of active aging be vigorously promoted. Concurrently, community infrastructure serves as the foundation for the mutual promotion of online and offline activities. Attention should be given to the development of infrastructure for an age-friendly environment. These findings deepen the understanding of the consequences of interactions between online and offline activities, subjective mindsets, and objective environments for older adults.